The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s10212-020-00471-8
|View full text |Cite
|
Sign up to set email alerts
|

Investigating professed and enacted epistemic beliefs about the uncertainty of scientific knowledge when students evaluate scientific controversies

Abstract: Prior research on epistemic beliefs, that is, individuals' views about knowledge and knowing, has mainly focused either on individuals' professed beliefs (as reported in questionnaires) or on their enacted beliefs (as indicated during task processing). However, little is known about the relation between professed and enacted epistemic beliefs. The present study focused on beliefs about the uncertainty of scientific knowledge and investigated both professed and enacted beliefs in the context of evaluations of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 77 publications
1
4
0
1
Order By: Relevance
“…Additionally, as a relation exists between epistemological beliefs and argumentation (Fischer et al, 2014), we did not only consider measures of epistemological beliefs but also a measure of argumentation as a form of enacted epistemological beliefs; cf., [6,35]. This is in line with Klopp and Stark [9], who also use a measure of argumentation.…”
Section: Hypothesis 4 (H4)supporting
confidence: 77%
“…Additionally, as a relation exists between epistemological beliefs and argumentation (Fischer et al, 2014), we did not only consider measures of epistemological beliefs but also a measure of argumentation as a form of enacted epistemological beliefs; cf., [6,35]. This is in line with Klopp and Stark [9], who also use a measure of argumentation.…”
Section: Hypothesis 4 (H4)supporting
confidence: 77%
“…Concerning the mediating role of metacognition, PISA-related studies have also shown metacognition to be a strong mediator between various independent variables and students’ digital reading achievement; for example, metacognition positively mediated the relationship between information-seeking reading activities (e.g., Lee & Wu 2013 ; Wu, 2014 ) and students’ digital reading performance. Narrowing the discussion to a specific type of metacognition, metacognition of assessing credibility is particularly important for students to navigate the sea of digital information (e.g., Abendroth & Richter, 2021 ; Lang et al, 2021 ; Maier & Richter, 2013 ; Mason et al, 2010 ). Considering that the particular metacognitive process of assessing credibility was newly added to the latest round of the PISA in 2018, previous PISA-related research on metacognition has not engaged in discussions of this aspect, which provides a research impetus for the current study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has been noted that the additional complexities of hypertexts compared to printed texts require an additional metacognitive process (Coiro & Dobler, 2007 ) and dynamic adjustment of learning strategies (Hu, 2014 ). To address the challenges posed by the rich inventories of knowledge created by complex or even contradictory information online (Hahnel et al, 2018 ), it is essential for learners to metacognitively supervise the process of assessing credibility (e.g., Abendroth & Richter, 2021 ; Lang et al, 2021 ; Maier & Richter, 2013 ; Mason et al, 2010 ). Therefore, the role of metacognition in assessing credibility in students’ reading performance is particularly significant as a topic for further investigation in the digital era.…”
Section: Introductionmentioning
confidence: 99%
“…This expert was also present in the final third step, during which the construct of epistemic beliefs was discussed with an expert (associate professor) engaged in education of foreigners, plurilingualism, Czech language didactics, onomastics, and phraseology. The EBS was piloted (March 2021) on a sample of eight primary school teachers (seven women, one man) and five kindergarten teachers (four women, one man) through a cognitive interview (Karabenick et al, 2007): 5 For example: a 4-point Likert scale with 29 items for 10th graders in Germany (Kampa et al, 2016); 22 items for 11th and 12th graders in Namibia (Shaakumeni, 2019); merging two scales (C + D) into one in research with German university students (Lang et al, 2020).…”
Section: Translation Of the Ebsmentioning
confidence: 99%